1989
DOI: 10.1007/bf00172924
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the experimental model of transplanted C6 glioblastoma in wistar rats

Abstract: Establishing in vivo glioblastoma models from cell lines requires a very strict methodology, in order to obtain reproducible tumors presenting all the characteristics of human spontaneous glioblastomas. In this respect, we have developed a model of glioblastoma in Wistar rats by stereotaxic intracerebral transplantation of a 10 microliters suspension of 6 x 10(6) C6 cells grown in vitro. The tumor take was very high in these conditions, only 1 rat over 30 had no tumor. The median survival time varied from 14 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0
2

Year Published

1993
1993
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 14 publications
2
48
0
2
Order By: Relevance
“…These characteristics have led to the use of the C6/wistar model in experiments due to its similarity to the human GBM 5 . despite this similarity, other authors believe this model does not possess the same heterogeneity, immuno-histochemical characteristics or invasive capacity of the GBM 6 .…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…These characteristics have led to the use of the C6/wistar model in experiments due to its similarity to the human GBM 5 . despite this similarity, other authors believe this model does not possess the same heterogeneity, immuno-histochemical characteristics or invasive capacity of the GBM 6 .…”
Section: Resultsmentioning
confidence: 85%
“…some authors have reported that these cells in fact originated from wistar rats 6 , and were chemically induced in wistarFurth rats by exposure to N,N'-nitrosomethylureia 9 . other authors have described C6 cells as compatible with BdIX 10 and sprague-dawley rats 11 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transplantation of cultured C6 cells into the brains of rats by stereotaxic procedure produces intra-cerebral tumors representing as closely as possible the characteristics of spontaneous gliomas with good reproducibility [35]. C6/Lac Z cells which constitutively express the LacZ reporter gene were obtained from ATCC.…”
Section: Tumor Implantationmentioning
confidence: 99%
“…Rat C6 glioma cells are an experimental cell line that when injected into neonatal Wistar rats grow into an intracerebral tumor with pathological similarities to human glioblastoma (GBM) (Auer et al, 1981). This glioblastoma model was used in a variety of studies related to brain tumor biology including tumor growth (Nagano et al, 1993;San-Galli et al, 1989), invasion (Nagano et al, 1993;Bernstein et al, 1991;Chicoine & Silbergeld, 1995), and evaluation of the therapeutic efficacy of cancer treatments (Barth 1998). The glioma tumors were obtained by injection of C6 glioma cells suspension in brain parenchyma as described elsewhere (Grobben et al, 2002).…”
Section: Ftir Characterization Of Normal Brain Tissues and C6 Glioma mentioning
confidence: 99%